Insight Into the Molecular Mechanisms for Microcystin Biodegradation in Lake Erie and Lake Taihu - Krausfeldt, Lauren E.; Steffen, Morgan M.; McKay, Robert M.; Bullerjahn, George S.; Boyer, Gregory L.; Wilhelm, Steven W. (Frontiers in Microbiology, 2019)
Microcystins are potent hepatotoxins that are frequently detected in fresh water lakes plagued by toxic cyanobacteria. Microbial biodegradation has been referred to as the most important avenue for removal of microcystin from aquatic environments. The biochemical pathway most commonly associated with the degradation of microcystin is encoded by the mlrABCD (mlr) cassette. The ecological significance of this pathway remains unclear as no studies have examined expression of these genes in natural environments. Six metatranscriptomics studies from microcystin-producing Microcystis blooms were analyzed to assess the activity of this pathway in environmental samples. Seventy-eight samples were collected from Lake Erie, USA/Canada and Lake Tai (Taihu), China, and screened for the presence of mlr gene transcripts. Read mapping to the mlr cassette indicated transcripts for these genes were absent, with only 77 of the collective 3.7 billion reads mapping to any part of the mlr cassette. Analysis of the assembled metatranscriptomes supported this, with only distantly related sequences identified as mlrABC-like. These observations were made despite the presence of microcystin and over 500,000 reads mapping to the mcy cassette for microcystin production. Glutathione S-transferases and alkaline proteases have been previously hypothesized to be alternative pathways for microcystin degradation, and expression of these genes was detected across space and time in both lakes. While the activity of these alternative pathways needs to be experimentally confirmed, they may be individually or collectively more important than mlr genes in the natural environment. Importantly, the lack of mlr expression could indicate microcystin biodegradation was not occurring during sample collection, although any mechanism that would leads to this remains allusive. This study raises interesting questions about the ubiquity, specificity and locality of microcystin biodegradation, and highlights the need for the characterization of relevant mechanisms in natural communities to understand the fate of microcystin in the environment and risk to public health.